Optimization of metoprolol tartrate modified- release matrix tablet formulation using Eudragit NE as binder for metoprolol fluid bed granulation - Tomuta, Ioan; Alecu, Cristian; Dudas, Dana; E. Leucuta, Sorin (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this experimental work was to investigate the possibility of obtaining hydroxypropyl methylcellulose (HPMC) hydrophilic matrix extended-release dosage forms with metoprolol by using aqueous dispersions of Eudragit NE, as binders in fluid bed granulation. To evaluate the influence of formulation variables (levels of HPMC—Methocel K100 M and Surelease E7 19010) on drug release during a period of time of 12 hours, and on the kinetic release, a full factorial experimental design with two factors and three levels was used. The formulation factors were the granulation polymer concentration and the matrix-forming polymer concentration. The obtained results have shown that the percentage of the drug released during the 12 hours is influenced both by the Methocel ratio and the Eudragit NE ratio; increasing the ratios of Eudragit and Methocel leads to the decrease of the percentage of the released drug.The influence of Eudragit NE percentage is maximum at four and six hours, but the influence of Methocel K100 M concentration is almost the same at all sampling times; all studied formulations showed a kinetic release that fitted best with the Peppas model.